Contribution of maternal mosaicism to false-positive chromosome X loss associated with noninvasive prenatal testing. (12th December 2022) - Wan, Junhui; Li, Ru; Li, Fatao; Yu, Qiuxia; Wang, Dan; Sun, Xiuhong; Zhang, Yongling; Jing, Xiangyi; Tang, Xuewei; Chen, Guilan; Jiang, Fan; Li, Fucheng; et al.
Abstract: Objective: To report the frequency of maternal mosaicism contributing to false-positive chromosome X loss associated with noninvasive prenatal testing (NIPT) at a single center. Methods: Pregnancies undergone NIPT using massively parallel sequencing at Guangzhou Women and Children's Medical Center between February 2015 and May 2020 were included in this study. Fetal karyotyping, quantitative fluorescence PCR (QF-PCR) or microarray analysis was provided to patients with abnormal sex chromosomal aneuploidy (SCA) results for confirmatory testing, and QF-PCR was also employed to detect maternal sex chromosome status. Results: cffDNA testing of 40682 pregnancies revealed 86 cases with NIPT results positive for chromosome X loss (0.21%). Among the 86 high-risk cases, 73 women had undergone confirmatory testing in our center, whereas 13 declined. Of the 73 women verified by invasive prenatal diagnosis, 27.4% (20/73) were true positive cases including six cases of monosomy X, two cases of microdeletion of Xp22.33, one case of deletion Xq27.2q28, one case of 47, XXX and ten cases with fetal sex chromosome mosaicism. Of the remaining 53 patients with fetal normal results, 30 cases had undergone QF-PCR analysis of maternal white blood cells. QF-PCR indicated that 36.7% (11/30) patients had an altered or mosaic maternal sex chromosome status. Statistical analysis indicated that cell-free fetal DNA (cffDNA) concentration estimated by chromosome X in maternal mosaic cases was significantly higher than that in the non-maternal mosaicism group ( p  < .05) and was related to maternal mosaicism rate ( r  = 0.88, p  < .05). Conclusions: Our findings indicated that maternal mosaicism of sex chromosome was not uncommon in false-positive NIPT chromosome X loss cases. We recommend that this information should be disclosed to pregnancies during clinical counseling and maternal sex chromosome status should be confirmed for the cases with NIPT chromosome X loss.